Communicating through ancillary gestures: Exploring effects on coperformers and audiences - Siminoski, Anna; Huynh, Erica; Schutz, Michael (Human Technology, 2020)
Musicians make elaborate movements while performing, often using gestures that might seem extraneous. To explore these movements, we motion-captured and audio-recorded different pairings of clarinetists and pianists performing Brahms’ Clarinet Sonata No. 1 with two manipulations: (a) allowing the performers full vs. no visual feedback, and (b) allowing the performers full vs. partial auditory feedback (i.e., the clarinetist could not hear the pianist). We found that observer ratings of audio–visual point-light renditions discriminated between manipulations and refined this insight through subsequent audio-alone and visual-alone experiments, providing an understanding of each modality’s contribution. This novel approach of evaluating point-light displays of performances under systematically manipulated conditions provides new perspective on the ways in which ancillary gestures contribute to both performer communication and audience reception of live performances.